Effectiveness of Wordwall as a Gamification-Based Learning Medium in Enhancing Student Motivation and Learning Activities - Muh. Al Amin; Syam, Nurwahid; Juniarti Iryani (Universitas Muhammadiyah Makassar, 2026)
Low learning motivation and limited student engagement remain persistent challenges in elementary science education, particularly in abstract topics such as light and sound. Conventional instructional approaches often fail to involve students, resulting in suboptimal learning experiences. In response to this issue, gamification-based digital learning media have emerged as a promising alternative to enhance student motivation and learning activities. This study aims to examine the effectiveness of Wordwall, a gamification-based learning medium, in increasing motivation and engagement in science learning among elementary school students. A mixed-methods approach with a sequential explanatory design was employed. Quantitatively, a true-experimental pretest–posttest control-group design was used with two Grade V classes at an elementary school in South Sulawesi, Indonesia, involving 50 students, equally divided into experimental and control groups. The experimental group received instruction using Wordwall, while the control group was taught using conventional methods. Data were collected using a learning motivation questionnaire and an observation sheet for learning activities. Qualitatively, phenomenological interviews were conducted with teachers and students to explore their learning experiences. The quantitative results showed that students in the experimental group experienced a significantly higher increase in learning motivation (21.37%) and learning activities (22.19%) compared to the control group (8.49% and 11.81%, respectively), with statistically significant differences confirmed by t-tests and ANOVA (p < 0.05). Qualitative findings supported these results, indicating that Wordwall created a more interactive, enjoyable, and engaging learning environment that encouraged active participation and sustained attention. The novelty of this study lies in integrating a true-experimental design with a qualitative phenomenological analysis to comprehensively examine the motivational and behavioral aspects of learning in elementary science education. In conclusion, Wordwall is an effective gamification-based learning medium for enhancing students’ motivation and engagement in science learning, and this study provides empirical evidence for the development of gamification-based instructional models in physics education at the elementary level.